The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4317/medoral.22802
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the distance from the cementoenamel junction to the bone crest and the thickness of the facial bone in anterior maxillary teeth: A cross-sectional tomographic study

Abstract: Background: The purpose of this cross-sectional study was to evaluate radiologically, the relation between the distance from the cementoenamel junction (CEJ) to the facial bone crest (FBC), and the facial alveolar bone (FAB) width at maxillary anterior teeth. A further aim was to assess if the CEJ-FBC distance had an impact in the prevalence to find a FAB thickness greater than one mm. Study design: CBCT images were retrospectively obtained from the database of the Oral Surgery Unit of the University of Valenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Rojo-Sanchis et al [44] substantiate an inverse relationship between the CEJ-BC distance and alveolar BCT through their tomographic study. Meanwhile, in this study, a reduction in the mean maxillary BCT in the case group was observed, compared with controls but not to a statistically significant degree.…”
Section: Discussionmentioning
confidence: 91%
“…Rojo-Sanchis et al [44] substantiate an inverse relationship between the CEJ-BC distance and alveolar BCT through their tomographic study. Meanwhile, in this study, a reduction in the mean maxillary BCT in the case group was observed, compared with controls but not to a statistically significant degree.…”
Section: Discussionmentioning
confidence: 91%
“…In a cross-sectional study based on CBCTs images, they concluded that the greater the distance between the CEJ and the bone crest is, the thinner the buccal cortical is ( 22 ). In this sense, in a review article conducted by Rojo-Sanchis et al .…”
Section: Discussionmentioning
confidence: 99%
“…Progressive periodontal attachment loss throughout life also results in an increased CEJ-FBC distance [ 16 ]. A recent study has published an inverse relationship between CEJ-FBC distance and FAB thickness at anterior maxillary teeth [ 54 ]. Even some authors have also associated shorter CEJ-FBC distances with thicker gingival biotype [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%